2018
DOI: 10.1139/cjc-2017-0487
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II) complexes bearing (NNN) ligand: catalytic evaluation of different solvent-mediated coordination modes

Abstract: A new (NNN) tridentate ligand was prepared, and its ability to coordinate ruthenium(II) was evaluated. The presence of different functional groups on the ligand allows bi- or tri-coordinated complexes to be obtained depending on complexation conditions. The catalytic activity of both bidentate and tridentate complexes was studied in asymmetric transfer hydrogenation of different aryl ketones, showing a comparable behavior of the two complexes in terms of efficiency and stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…78 In 2018, Rimoldi and co-workers reported chiral NNN-L17 which derived from chiral diamine and proline. 79…”
Section: Nnn-type Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…78 In 2018, Rimoldi and co-workers reported chiral NNN-L17 which derived from chiral diamine and proline. 79…”
Section: Nnn-type Ligandsmentioning
confidence: 99%
“…137 In 2000, Braunstein 82 and co-workers reported the complexation of NPN-L3 and [RuCl 2 (p-cymene)] 2 , and dimerized ruthenium complex NPN-Ru-1 was separated and characterized. In 2018, Rimoldi 79 and co-workers prepared dimerized NNN-Ru-6 by reacting NNN-L17 with the same ruthenium precursor (Scheme 4). In 1994, Nishiyama prepared NNN-Ruethylene by reacting i-Pr Pybox with [RuCl 2 (p-cymene)] in the presence of ethylene.…”
Section: Ruthenium and Osmiummentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Compound 44 was also used as a template for the development of peptidebased catalysts in Henry reactions [38] and asymmetric transfer hydrogenations. [39] Among δ-AAs, Geyer's research group reported on the synthesis of the bicyclic core-non coded AA 46, used as β-turn mimic (Figure 7). [40] In particular, they synthesized different peptidomimetics mimicking Foldon β-hairpin protein by using 46 instead of AspÀ Gly loop that does not stabilize in a proper way the natural β-hairpin, essential for Foldon protein function.…”
Section: Delta Aasmentioning
confidence: 99%
“…To enhance the catalytic performance of asymmetric catalytic boron conjugate addition, tripodal ligands, based on the tetrahydroquinoline or quinolone scaffold, were incorporated into the Cu II complexes. This successful combination led to keto–alcohol derivatives in an enantiomerically enriched form.…”
Section: Introductionmentioning
confidence: 99%